O processo civil coletivo e as condições da ação - João, Ivone Cristina de Souza (2007)
PURPOSE(s): This research intends to offer suggestions of application in the current gaps found in the action conditions in each kind of collective action and in each kind of collective right. JUSTIFICATION(s): The subject is relevant because collective actions are part of the development in process right in the search for the instrumentality of the process and the universality of jurisdiction. HYPOTHESES: Presuppositions forming the basis for reasoning here rooted in the meaning of action conditions - legal possibility of request, legitimacy of parts and unfolded to benefiting, adequacy or modification of such conditions in the application at the collective process. THEORETICAL AND METHODOLOGICAL ASPECTS: The research comprises the whole doctrinal and legislative material on the theme, with deep jurisprudential investigation, chiefly at the national files of the Brazilian judiciary system and State Courts from three important states in Brazil. RESULTS: The research brought about ideas expected to conduce to the use of collective actions, to the bills of collective process legislation in course or still to the perfectioning of the legislation in force